Advances in PassDop technology: recombination and optics. (September 2017) - Steinhauser, Bernd; Büchler, Andreas; Nagel, Henning; Gutscher, Simon; Kluska, Sven; Benick, Jan; Saint-Cast, Pierre; Bartsch, Jonas; Hermle, Martin
Abstract: The PassDop technology is a promising approach to realize passivated emitter and rear locally diffused (PERL) silicon solar cells within a reasonable process sequence. In previous studies, the feasibility of this concept was evaluated, but two topics were only briefly discussed: the recombination at the locally diffused and contacted surface and the optical layer. In this study we present an analysis of the recombination at laser processed spots of local laser diffusion from a-SiNx :P. We show that initially the local recombination prefactor J 0b, met for the metallized area is very high (10 4 fA/cm 2 ) but a dedicated anneal can be used to reduce the recombination to a competitive level (600 fA/cm 2 ). The improvement was allocated to the inner area of the laser-processed spot by measuring μ-PL before and after annealing. To improve the optics we show that SiOx can be used on the rear if an etch-back is applied after the laser diffusion. Applying SiOx, results similar to the reference MgF2 layer for J sc and FF were achieved, while providing much improved adhesion. Finally, we show large area n -type silicon solar cells featuring a PassDop rear side as well as laser contact opening in combination with nickel- and copper-plating on the front. Combining these technologies, we were able to achieve an energy conversion efficiency of 22.2 %.